Composição Química e Características Fermentativas de Silagens de Cana-de-Açúcar Contendo Farelo de Babaçu - Rezende, A. A S; Pascoal, L. A F [UNESP]; van Cleef, E. H C B [UNESP]; Gonçalves, J. S. [UNESP]; Olszevski, N.; Bezerra, A. P A (My University, 2011)
The objective of this trial was to evaluate the effect of babassu meal addition on chemical composition and fermentative characteristics of sugar cane silages. The addition of three concentrations of babassu meal (0; 15 and 30% in fresh matter) was evaluated in a completely randomized design with four replicates. As experimental silos 12 plastic buckets were used, provided with filter closing to allow the exit of fermentation gases. After 45 days, the silos were opened and samples were taken for the determination of dry matter (MS), crude protein (PB), neutral and acid detergent fibers (FDN, FDA) and hemicelluloses (Hem) content, pH values, total acidity quantification (ATT), losses by gases (PG) and effluents (PE). The addition of babassu meal increased the MS contents (38.4% e 40.6%), PB (7.8 e 8.9%), FDN (68.8% e 70.9%) and FDA (43.0% and 45.1%), respectively, with the addition of 15 and 30% of the by-product. The pH values, averaged 4.4, were not affected by the addition of babassu meal. The percentage of ATT increased 89.2%. PG and PE were reduced in 44.8 and 58.8%, respectively. The addition of babassu meal have contributed to the improvement of fermentative parameters and the concentration of CP in the sugar cane silages. However, its use as additive becomes limited due to the increase in fiber content that provides to the silages, depreciating its nutritive value.
Chemical composition and fermentative characteristics of sugar cane silages containing babassu meal
Keywords: By-product; Losses; Orbignya barbosiana; Saccharum